Evaluation of user experience on customer services mobile application - Yue Hock, Sim; Omar, Ridha; Mahmud, Murni (Universiti Tenaga Nasional, 2017)
The User Experience factor is an important facet of today’s mobile application interface design. The functionalities, contents and services provided by the application will affect the experience of users who use these mobile applications. This paper intends to discuss the evaluation process of mobile application for consumer-related services. The researchers will then deliberate on the analysis done, and the respective results will also be presented.